Integrasi Pendekatan Kualitatif Dan Kuantitatif Dalam Penilaian Estetika Fasade Bangunan Di Koridor Jalan Kayutangan, Malang - Santosa, Herry; Suryasari, Noviani; Mustikawati, Triandriani (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2015)
Urban streetscape is a reflection of the visual appearance of urban space that represents the character of the City Image as well as an architectural embodiment of the cultural heritage of the city that are essential to be preserved, maintained continuity and sustainability with the architecture civilization of the past, present and future. Due to the rapid growth of trade and service area in kayutangan corridor as one of the conservation streetscape, the strict control of the visual appearance in Kayutangan corridor is indispensable. Building facade is one of the keys to an architectural visual that can be used as a conservation guidance for the visual order of kayutangan corridor. The efforts to control the building facade can be performed by study on aesthetic evaluation. The aesthetic evaluation can be performed in two studies approaches, namely a qualitative and quantitative research methods. This study utilizes a combination of the use of qualitative methods through preferences people method and a quantitative method through Interface Aesthetic Measurement (IAM) software. The utilization of both methods is intended to produce an accurate study of visual evaluation of the building facade and a reference for the development of Interface Aesthetic Measurement (IAM) software in assessing the aesthetic element of building visual in similar cases.Keywords: Aesthetic, Facade, Visual Evaluation, Conservation